Efficiency and tolerance of acne therapy using system isotretinoin - Yu. N. Perlamutrov; K. B. Olkhovskaya; M. M. Kokhan; Yu. V. Keniksfest; Yu. B. Shaibakova; N. V. Polyakova; E. P. Topychkanova; Ya. V. Kashcheeva; A. V. Samtsov; A. V. Statsenko; I. E. Belousova; V. R. Khayrutdinov; et al. (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Purpose. Determination of efficiency and tolerance of Sotret product in treatment of patients with different clinical forms and severe acne in three clinical investigations. Materials and methods. 103 patients with acne (moderate and severe acne, acne conglobata and acne inversa) were examined and treated. All patients underwent monotherapy with Sotret with clinical effectiveness assessment and records of adverse events. Results. Sotret therapy facilitated clinical remission of acne in 90-100% of cases. Adverse events were easily tolerated and were not serious. Conclusion. Established therapeutic efficiency of Sotret determines its potential in treating various severity and various forms of acne.